Productivity Development and Marketing of Janggelan, Mesona palustris in Jeruk Village, Bandar District, Pacitan Regency - Ratna Mustika Wardhani (Gontor AGROTECH Science Journal, 2020)
Janggelan (Mesona palustris BL) is usually used for making black grass jelly, but can also be used for cosmetic ingredients. Increasing production through intensification programs requires farmers' understanding of the problem of janggelan. Problems are not only limited to cultivation techniques, but also include problems with the introduction of plants, their uses, nutritional value and market potential. The research objective was to determine the potential of janggelan and to analyze the janggelan farming and marketing channels in Jeruk Village, Bandar District, Pacitan Regency. This research uses analytical methods and its implementation with survey techniques. The method of determining the research area used purposive sampling method, namely in Jeruk Village, Bandar District, Pacitan Regency. Determination of the number of samples using the random sampling method. The data used are primary data and secondary data. The data collection technique was done by taking notes, observing and interviewing. The results showed that the productivity of Janggelan plants in Jeruk Village, Bandar District, Pacitan Regency, has the potential to develop Janggelan plants (Mesona palustris BL) and there are 4 (four) marketing channels carried out to market Janggelan plants (Mesona palustris BL).